Investigations on Carabid Beetles in Friuli vineyards with different agronomical practices (Bollettino di zoologia agraria e bachicoltura, 2024)
The results are given of an investigation of the geophilous fauna, with particular reference to Carabid Beetles carried out during the period March 1984 to April 1985. The survey was made in two vineyards in Friuli (North-East Italy), one at Azzano Decimo (Pordenone) and the other at Pantianicco (Udine).In the former the observations were made on four plots of land characterized by: ground completely covered with a blanket of grass which had never been mown (MIA); ground periodically worked (PGLA); periodically mowed grass covered ground between rows of vines (TA); not treated with insecticides since the winter of 1983-84 (TNTA).The four plots on the second farm, denoted by the symbols CP, PGP, TP and TNTP were grass covered and mowed between the rows of vines as well as weeded in the vicinity of the vine plants; in particular TNTP had not been treated with insecticides since the winter of 1983-84.A pitfall traps was used to collect the arthropod fauna. The numbers of captured insects are expressed as "activity density"; in order to obtain a similarity scale between the two biotopes the Sorensen and Renkonen index was used. The differences found between the two biotopes, in regard to the presence and composition of the soil arthropods, are due to various factors, for example the type of soil and the different agronomical methods adopted in the two vineyards. Among the Carabid species found 13 were only present in the clay type soil of Azzano Decimo, 9 only in the sandy loam stony soil of Pantianicco and just 18 species common to both places.Nebria brevicollis, Clivina fossor, Chlaenius nitidulus, Stenolophus teutonus, Harpalus distinguendus, were among the species found exclusively on the farm at Azzano Decimo while Harpalus rubripes and Calathus melanocephalus were among those found only at Pantianicco. Carabus germari, Ophonus subquadratus, Harpalus rufipes, H. affinis, Amara spp., Calathus fuscipes, Agonum dorsaleand Brachinus explodens were found in both places.The presence of grass, whether mown or not, favours certain species such as Carabus germari and Harpalus rufipes, while working the soil increases the density of activity of other species, for example Harpalus distinguendus, Pterosticus macer, P. melanarius, P. melas and Brachinus sclopeta.Suspension of insecticide treatment leads to an increase in the number of individuals but not in the number of species.It is of the utmost importance to know the Carabid fauna of the "vineyard" agroecosystem in order to study the predatory activity of these insects upon phytophagous insects of vines.